2017
DOI: 10.1016/j.mcat.2017.09.029
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the alkoxycarbonylation of propargyl alcohol

Abstract: The challenging carbonylation of propargyl alcohol is effectively catalyzed by Pd(OAc)2 in combination with diphenyl-(6-methyl-pyridin-2-yl)phosphine and methanesulfonic acid. In dichloroethane at 20–50 ◦C, the reaction affords with almost complete regioselectivity alkyl 2-(hydroxymethyl)acrylates. Turnover frequency numbers (TOF) of up to 450 h−1 can be achieved working at 50 ◦C, while a maximum turnover number (TON) of about 730 is obtained at 30 ◦C. The catalyst longevity is limited because the carbonylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In initial experiments (Scheme 3 and Table 1), the methoxycarbonylation of trimethylsilylacetylene was carried out in the presence of the catalytic system Pd(OAc) 2 / CH 3 SO 3 H/PyPPh 2 . The adopted reaction conditions were those usually employed with Drent's catalyst [9,10,12,24] that imply the use of an excess of the phosphine, reaction temperature in the 50 C to 80 C range, P(CO) in the 10to 50-atm range.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In initial experiments (Scheme 3 and Table 1), the methoxycarbonylation of trimethylsilylacetylene was carried out in the presence of the catalytic system Pd(OAc) 2 / CH 3 SO 3 H/PyPPh 2 . The adopted reaction conditions were those usually employed with Drent's catalyst [9,10,12,24] that imply the use of an excess of the phosphine, reaction temperature in the 50 C to 80 C range, P(CO) in the 10to 50-atm range.…”
Section: Resultsmentioning
confidence: 99%
“…[9,10] When applied to terminal alkynes (see Scheme 1), the process usually proceeds with high regioselectivity (e.g., >95%) towards the branched product allowing to obtain in one step 2-substituted-α,β-unsaturated carboxylic esters that are key intermediates in industrial [11] and fine chemistry. [12,13] Works by Drent other researchers and us [8][9][10][11][13][14][15][16][17][18][19] showed that the presence of the 2-pyridyl group in the phosphino ligand plays a crucial role, because when such type of group is not present, the efficiency of the catalytic system is by far lower.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the activity of M(0)NPs-CS and optimize hydrogenation reaction conditions, preliminary experiments were carried out using (E)-cinnamaldehyde (I) as a model substrate and relevant data are reported in Table 1. As previously mentioned, the hydrogenation of (I) is challenging due to the possible formation of several by-products [44,[80][81][82][83][84][85] and is often chosen as model reaction considering both its scientific and industrial relevance [84][85][86][87].…”
Section: Catalytic Hydrogenation In the Presence Of M(0)nps-csmentioning
confidence: 99%
“…24 The chelate bidentate coordination of the Ph 2 PPy ligand gives rise to a relative strained four-membered metallacycle which stabilizes some crucial intermediates in several processes catalyzed by the system Pd(OAc) 2 /PPh 2 Py/H + such as the methoxycarbonylation of propyne, 25 the hydrocarboxylation of acetylene 26 or the alkoxycarbonylation of alkynols. 27 However, the key of the high efficiency of these catalytic systems is likely the active role of the ligand as a "proton messenger" (P-N/P-NH + ) promoting fundamental steps of the catalytic cycle.…”
Section: ■ Introductionmentioning
confidence: 99%